The Effect of a 20-Hour Baby-Friendly Hospital Initiative Training Program on Nurses' Breastfeeding Knowledge, Attitudes and Confidence, in a Tertiary Hospital in Singapore. - Fok, Doris (Georg Thieme Verlag KG, 2020)
10.1055/s-0040-1716489